e-LivestockProv: An Architecture based on Provenance to Manage Traceability in Precision Livestock Farming - Gomes, Jonas S.; David, José Maria N.; Braga, Regina; Arbex, Wagner; Barbosa, Bryan; Gomes, Wneiton Luiz; Fonseca, Leonardo M. Gravina (Anais do Workshop de Práticas de Ciência Aberta para Engenharia de Software (OpenScienSE); 2021: Anais do I Workshop de Práticas de Ciência Aberta para Engenharia de SoftwareDO - 10.5753/opensciense.2021.17145, 2021)
The use of sensors in the agricultural sector generates a large volume of heterogeneous data that must be processed, stored, and analyzed to support decisions. In addition, decisions taken in agriculture need to be traceable due to the diversity of data and devices present in different agricultural contexts. With provenance, we can trace and analyze data to improve future decisions and avoid the usefulness ones. This article presents the e-LivestockProv architecture, focusing on data provenance.